KNOWLEDGE AND PRACTICES OF NURSING STUDENTS TOWARDS KANGAROO MOTHER CARE (KMC) AMONG TWO SELECTED NURSING INSTITUTIONS IN MBARARA MUNICIPALITY. A CROSS-SECTIONAL DESCRIPTIVE STUDY. - Natwijuka, Andrew; Lukowe , Hadijah (Student's Journal of Health Research Africa, 2023)
Background: Globally 25 million infants (17%) are born with a low birth weight (LBW) and most of these occur in low-income countries. LBW infants suffer from high rates of morbidity and mortality. Therefore low-income countries have recognized kangaroo mother care (KMC) as a necessity to promote positive neonatal health under adverse conditions. Methods: A cross-sectional study was conducted using a quantitative approach. A total of three hundred twenty-six (326) nursing students participated in the study and they were selected by simple random sampling method. Data were collected through self-administered questionnaires. Data were checked for completeness, cleaned, and entered in SPSS for further analysis. Data analysis was conducted by using descriptive statistics and a chi-square test to show the association between variables. Results: Three hundred nineteen (319) fully completed the study, yielding a response rate of 97.8%. The majority of subjects were aged between 24 to 29 years (34.8%), belonged to the protestant religion (40.8%) and there were more females (56.4%). The majority of the nursing students were pursuing a certificate level of Ugandan education (29.5%) and most of them had two years of studying (52.6%). students in the second year (49.2%) had the highest percentage of nursing students with good to excellent knowledge as compared to the rest. Characters of age (P value=0.001), religion (P value=0.000) course of study (P value=0.000), and year of study (P value=0.007) were found significant with knowledge of nursing students on KMC. Recommendations:. It is crucial to establish suitable guidelines and a specialized Kangaroo Mother Care unit in all health facilities in Uganda. Conclusion: The general level of knowledge and behavior toward KMC was deemed adequate.